2010
DOI: 10.1007/s10528-010-9337-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a QTL for Adipocyte Volume and of Shared Genetic Effects with Aspartate Aminotransferase

Abstract: Plasma levels of Aspartate aminotransferase (AST), a liver enzyme, are elevated in patients with visceral obesity. The purpose of this study was to examine if adipocyte volume is under the influence of genetic factors and to evaluate its genetic correlations with AST. Fasting plasma of 374 pedigreed baboons from the Southwest National Primate Research Center at the Southwest Foundation for Biomedical Research, San Antonio, TX were assayed for AST. Adipocyte volume was measured using biopsies of omental adipose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Dietary fructose also results in hepatic steatosis and inflammation in Old World monkeys 367 and increases liver triglyceride and cholesterol content in rhesus macaques. Studies investigating the pathogenesis of fatty liver disease have also been performed in baboons and marmosets [368][369][370] . Importantly, DIO non-human primate models have proved valuable in evaluating the therapeutic potential and/or safety of a number of interventions, including tyrosine-protein phosphatase non-receptor type 1 antisense oligonucleotides 371 , fibroblast growth factor 21 372,373 , glucagon-like peptide 1 agonists 374 , omega-3 fatty acids 366 , melanocortin receptor 4 agonists 375 , tropomyosin receptor kinase B agonism 376 and oxytocin administration 377 , in the treatment of obesity, insulin resistance and obesity-related metabolic diseases.…”
Section: Diet-induced Glucose Intolerance Yes Yesmentioning
confidence: 99%
“…Dietary fructose also results in hepatic steatosis and inflammation in Old World monkeys 367 and increases liver triglyceride and cholesterol content in rhesus macaques. Studies investigating the pathogenesis of fatty liver disease have also been performed in baboons and marmosets [368][369][370] . Importantly, DIO non-human primate models have proved valuable in evaluating the therapeutic potential and/or safety of a number of interventions, including tyrosine-protein phosphatase non-receptor type 1 antisense oligonucleotides 371 , fibroblast growth factor 21 372,373 , glucagon-like peptide 1 agonists 374 , omega-3 fatty acids 366 , melanocortin receptor 4 agonists 375 , tropomyosin receptor kinase B agonism 376 and oxytocin administration 377 , in the treatment of obesity, insulin resistance and obesity-related metabolic diseases.…”
Section: Diet-induced Glucose Intolerance Yes Yesmentioning
confidence: 99%
“…The first-generation linkage map was published in 2000 [35] and later improved in 2006 by the addition of more loci in chromosomal regions with insufficient marker density in the initial map [36]. This map has allowed scientists to localize and identify functionally significant genes that influence phenotypic variation related to human health or disease [11], [14], [37][42].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that AST levels and fat cell volume are influenced by common set of genes in baboons, a valuable non-human primate model for the study of obesity and its comorbidities. 25 26 …”
Section: Discussionmentioning
confidence: 99%